(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Hydrogen production from biomass may become one of the leading areas of bioenergy in Ukraine soon.Currently, the main direction of biomass energy production in Ukraine is the production of thermal energy for distributed heat supply of enterprises and private households by burning biomass of wood and agricultural origin. Nowadays in Ukraine, there is a technology for the production of biohydrogen. We calculated the environmental and economic effects of hydrogen production as a source of energy. We have come up with the following conclusion that if there is a demand for the final product, hydrogen production will be attractive from economic standpoint and will not require a green tariff or other support from the government.The market price of biohydrogen will be 4-5 per kg and will be comparable to that which the European Union aims to achieve.We assume that hydrogen may be a cleaner source of energy for end users, especially in the transport sector in the future.One of the main issues of Ukraine's possible participation in Europe's hydrogen energy program as a supplier and producer of renewable hydrogen is the possibility of its technically safe and cost-effective transportation to EU countries.As the main hypothesis considered transportation of hydrogen using the gas transmission system of Ukraine as part of a mixture with natural gas. Calculations show that, of course, obtaining energy from hydrogen, even in mass production, will be more expensive than alternative traditional and non-traditional methods. The development of this technology, in any case, is promising in terms of the development of energy independence and environmental development of states. The effect of scale in mass production of hydrogen energy should also work, which will significantly reduce the cost of this technology.